Respuesta :

-3b=-a-2c
b=(a-2c)/-3

Answer:

[tex]b=\frac{a+2c}{3}[/tex]

Step-by-step explanation:

We have been given an equation [tex]a=3b-2c[/tex]. We are supposed to solve the given equation for b.

First of all, we will switch sides of the given equation as:

[tex]3b-2c=a[/tex]

Let us add [tex]2c[/tex] on both sides:

[tex]3b-2c+2c=a+2c[/tex]

[tex]3b=a+2c[/tex]

Divide both sides by 3:

[tex]\frac{3b}{3}=\frac{a+2c}{3}[/tex]

[tex]b=\frac{a+2c}{3}[/tex]

Therefore, our required equation wold be [tex]b=\frac{a+2c}{3}[/tex].